(untitled) (Trabalho & Educação, 2018)
The recent research has as main target the professional education to young and female teenagers in socio-educational measure fulfillment of confinement in the state of Minas Gerais, and aims to unveil how it is offered the professional education to these young and teenagers, as well how to identify the perceptions of the inmates about the offered courses and their expectations about work after confinement period. Inserts in “Line II: Training processes of technology education” from the program of Post-Graduation in Technology Education CEFET – MG which has as an objective study the training processes of the Technology Education area, in a omnidirectional perspective, so as among the educational and organizational institutions, as in the exercise of its own work. It is about a qualitative research, which the review of the literature pass through studies about the youth in social vulnerability, the history and legislation of the Brazilian socio-educational system, the professional education inside socio - educational measures and the gender relations in the social - educational measures. Knowing that there are few studies that talk about this theme, several researches on specific themes have been used to reach the legislation that regulates educational practices in social-educational measures, highlighting studies of Castro and Abramovay (2002, 2006), Jeloás and Ferrari (2013), Constantino (2001), Costa (2006), Fialho (2016) and Julião and Abdalla (2013). The methodology used to data collect was composed of semi-structured interviews with three managers of the social-educational center: São Jerônimo –the only one which keeps youth and teenagers females in the state – and a section focus group with five kept teenagers. The data were analyzed using content analysis technique and reveal the expectative of the inmates related to the professionalization and work (jobs) are modest, reflecting their trajectory of life full of violence and social vulnerabilities. In its turn, the manage team efforts to offer professional courses of short time to the young’s sentenced, but face many hindrances and difficulties to meet their real needs. ___ A presente pesquisa tem como tema central a educação profissional para jovens e adolescentes do sexo feminino em cumprimento de medida socioeducativa de internação no estado de Minas Gerais e objetiva desvelar como se dá a oferta da educação profissional para essas jovens e adolescentes, bem como identificar as percepções das internas sobre os cursos ofertados e suas expectativas sobre o trabalho após o período de internação. Insere-se na “Linha II: Processos Formativos em Educação Tecnológica” do Programa de Pós-Graduação em Educação Tecnológica do CEFET-MG que tem por objetivo estudar os processos formativos na área da Educação Tecnológica, em uma perspectiva omnilateral, tanto nos âmbitos das instituições educacionais e organizacionais, quanto no exercício do próprio trabalho. Trata-se de uma pesquisa qualitativa, cuja revisão da literatura perpassa estudos sobre juventudes em vulnerabilidade social, a história e a legislação do sistema socioeducativo brasileiro, a educação profissional nas medidas socioeducativas e as relações de gênero nas medidas socioeducativas. Devido à carência de estudos que abordem esta temática foram utilizadas diversas obras sobre temas específicos até se chegar à legislação que regulamenta as práticas educativas nas medidas socioeducativas, destacando-se trabalhos de Castro e Abramovay (2002, 2006), Jeloás e Ferrari (2013), Águido (2011), Constantino (2001), Costa (2006), Fialho (2016) e, Julião e Abdalla (2013). A metodologia utilizada para coleta de dados foi composta por entrevistas semiestruturadas com três gestores do Centro Socioeducativo São Jerônimo - o único que acautela jovens e adolescentes do sexo feminino no estado, e uma seção de grupo focal com cinco adolescentes acauteladas. Os dados foram analisados utilizando-se a técnica de análise de conteúdo e revelam que as expectativas das internas em relação à profissionalização e ao trabalho são modestas, refletindo sua trajetória de vida repleta de violências e vulnerabilidades sociais. Por sua vez, a equipe gestora se esforça para ofertar cursos profissionalizantes de curta duração para as jovens sentenciadas, mas enfrentam muitos entraves e dificuldades para atender as suas reais necessidades.